Prehospital Hemorrhage Assessment Criteria: A Concise Review. Issue 5 (September 2021) - Di Carlo, Sara; Cavallaro, Giuseppe; Palomeque, Kenia; Cardi, Maurizio; Sica, Giuseppe; Rossi, Piero; Sibio, Simone
Abstract : Objective: Early assessment of the clinical status of trauma patients is crucial for guiding the treatment strategy, and it requires a rapid and systematic approach. The aim of this report is to critically review the assessment parameters currently used in the prehospital setting to quantify blood loss in trauma. Data Sources: Studies regarding hemorrhagic shock in trauma were pooled from PubMed, EMBASE, and Cochrane databases using key words such as "hemorrhagic shock, " "vital signs evaluation, " "trauma, " "blood loss, " and "emergency medical service, " alone or combined. Study Selection: Articles published since 2009 in English and Italian were considered eligible if containing data on assessment parameters in blood loss in adults. Data Extraction: Sixteen articles matching the inclusion criteria were considered in our study. Data Synthesis: Current prehospital assessment measures lack precise correlation with blood loss. Conclusions: Traditional assessment parameters such as heart rate, systolic blood pressure, shock index, and Glasgow Coma Scale score often lag in providing accurate blood loss assessment. The current literature supports the need for a noninvasive, continuously monitored assessment parameter to identify early shock in the prehospital setting.